Variabilidad de algunos parámetros fisicoquímicos y productividad primaria en la laguna La Cruz, Sonora, México - Valdez-Holguín, J Eduardo; Martínez-Cordova, Luis R (Revista de Biología Tropical, 1993)
time series analysis was used to determine the main factors influencing variability of sorne enviromental pararneters in two fixed points at the La Cruz Lagoon, Bahia Kino, Sonora, Mexico. Height of water colurnn and distance to the mouth were the main factors determining differences between the two sarnpling sites. The study showed thal spring and neap tides. and seasonal and annual cycles had a major influence on the variability of the parameters measured